Thermodynamic analysis of β-Ga2O3 growth by molecular beam epitaxy. (1st January 2023) - Togashi, Rie; Ishida, Haruka; Goto, Ken; Higashiwaki, Masataka; Kumagai, Yoshinao
Abstract: Thermodynamic analyses of β -Ga2 O3 growth by both ozone and plasma-assisted molecular beam epitaxy (MBE) were performed. In either case, the growth mechanism was found to differ depending on whether the input VI/III ratio was above or below 1.5. Under O-rich conditions (VI/III > 1.5), the driving force for β -Ga2 O3 growth ( Δ P Ga 2 O 3 ) was determined to increase linearly with increasing Ga input partial pressure ( P Ga o ) because almost all the supplied Ga was used for the growth of the β -Ga2 O3 . In contrast, Ga-rich conditions (VI/III < 1.5) caused Δ P Ga 2 O 3 to decrease. Etching of the β -Ga2 O3 occurred with increasing P Ga o due to the formation of volatile Ga2 O. This work also demonstrated that the use of ozone allowed growth at higher temperatures than the use of O radicals. The calculated results were in good agreement with experimental values, indicating that β -Ga2 O3 growth by MBE can be explained by thermodynamics.